(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article examines the dynamics of the development of motor qualities in athletes practicing CrossFit. It analyzes modern approaches to the training process, the peculiarities of the body’s adaptation to high-intensity physical loads, as well as the efficiency of using CrossFit methodologies in sports training. One of the innovative types of motor activity is CrossFit, which in recent times has gained wide popularity among all segments of the Ukrainian population. Its uniqueness lies in its variability, its wide spectrum of impact on the body’s main systems, and the combination of exercises from various sports such as weightlifting, kettlebell training, gymnastics, athletics, and more. Despite the popularity of CrossFit among both professional athletes and amateurs, the question of its impact on the dynamics of motor quality development remains insufficiently studied in the scientific literature. In particular, there is a lack of systematic research that evaluates the biomechanical, physiological, and neuromuscular adaptation mechanisms formed under the influence of regular CrossFit training. It has been determined that as a modern sport, CrossFit should become an important and necessary stimulus for the systematic participation in and conduct of training sessions by athletes of various physical fitness levels, thereby contributing to the development of their motor qualities. However, scientific research in this area is still lacking, which makes the study of the dynamics of motor quality development in CrossFit highly relevant. The research is based on the analysis of control and experimental groups of athletes from Youth Sports School No. 1 and the “SV-CLUB” sports club in Khmelnytskyi. It was found that CrossFit significantly improves strength, endurance, speed, and coordination. The research results demonstrated that CrossFit is an effective methodology for the development of motor qualities in athletes, ensuring significant improvements in strength, endurance, speed, coordination, and flexibility. A comparative analysis with the control group showed that traditional general physical training methods are less effective in achieving a comprehensive improvement in physical characteristics.